The Paradoxical Influence Of Job Insecurity On Workplace Satisfaction: Evidence From Indonesian Migrant Workers In Sarawak, Malaysia - Wanty Eka Jayanti; Wanty Eka Jayanti; Muhammad Irfani Hendri; Titik Rosnani (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: This investigation addresses a critical gap in understanding how employment uncertainty influences job contentment among cross-border laborers. Conventional wisdom suggests that feelings of workplace instability diminish employee satisfaction; however, preliminary observations among Indonesian migrant workers (PMI) in Sarawak reveal a counterintuitive pattern. The primary objective examines whether employment precariousness paradoxically enhances occupational fulfillment within this unique demographic context.Methodology: A sequential explanatory mixed-method framework was implemented. Initially, quantitative data from 207 Indonesian migrant workers in Sarawak underwent structural equation modeling analysis using PLS-SEM techniques. Subsequently, qualitative validation occurred through in-depth interviews with ten purposively selected informants, exploring psychological mechanisms underlying the observed statistical relationships. The integration triangulated numerical evidence with contextual narratives.Finding: Statistical analysis revealed an unexpected positive correlation (β=0.161, p=0.009) between employment insecurity and job satisfaction, contradicting mainstream theoretical predictions. Four distinct psychological mechanisms emerged through qualitative analysis: gratitude amplification (30% of informants), comparative advantage recognition (30%), motivational intensification (20%), and existential meaning reinforcement (20%). Work-related factors demonstrated the strongest predictive power (β=0.655, p<0.001), while fear of social judgment exhibited dual pathways, directly influencing satisfaction (β=0.133, p=0.026) and indirectly through insecurity perceptions. The integrated model explained 85.2% variance in job satisfaction.Conclusion: Employment uncertainty operates paradoxically among migrant populations, transforming potential stressors into satisfaction enhancers through context-specific psychological adaptations. This challenges universalist assumptions in job insecurity theory and demonstrates the necessity for culturally situated frameworks when examining transnational labor dynamics. Practical implications suggest that policies addressing migrant worker welfare should prioritize tangible workplace conditions over exclusively targeting security perceptions, as insecurity may function protectively within constrained opportunity structures.